From event to performance function-based resilience analysis and improvement processes for more sustainable systems. (14th June 2021) - Häring, Ivo; Schäfer, Johannes; Vogelbacher, Georg; Fischer, Kai; Riedel, Werner; Faist, Katja; Finger, Jörg; Fehling-Kaschek, Mirjam; Scharte, Benjamin; Ross, Katharina; Restayn, Elena-Maria; Stolz, Alexander; et al.
Rising extremes and varieties of threats towards socio technical systems ask for improved overall risk control and resilience enhancement. Most current classical approaches focus on the assessment of single or multiple threat events countering system objectives. However, more recent approaches ask for the identification, determination and use of time-dependent system performance functions and their assessment in case of disruptions. Thus, the paper discusses advanced risk and resilience analysis approaches for explosions, terroristic events in urban spaces, cascading effects in coupled supply grids, scoring of critical infrastructures, and tabular resilience analysis and management. Summarising respectively the main processes, methods for steps and results, it argues how time-dependent system performance function resilience approaches allow a more direct quantification of overall risk control objectives, since it assesses main system service functions before, during and post disruptions. The approaches are well suited for communication with the public, management and dashboard mobile visualisation.